A Late Post-Glacial environmental record and Early Neolithic intertidal peat land surface at Porth Neigwl, Llŷn Peninsula, Gwynedd. (1st December 2016) - Caseldine, Astrid; Griffiths, Catherine; Jones, Sarah; Peck, Inga; Smith, George
This paper describes the recording and palaeoenvironmental study and dating of a small area of intertidal peat deposit which has produced a retouched stone tool of probable Early Neolithic date.